The Urgency of the Principle of Balance in the Service Bond Agreement of Lion Air Group - Maria Mu’ti Wulandari; Ulil Afwa; Putri Ayu Sutrisno (LEGAL BRIEF, 2024)
The concept of balance is vital in work contracts, where mutual fulfillment of rights and obligations ensures justice. Specifically, this study will focus on the balance principle within the service bond work agreement at Lion Air Group, by examining its relevance and the legal protection it offers to pilots. Utilizing a normative juridical approach, the research analyzes the Lion Air Group Service Association Work Agreement. Findings reveal that the agreement between PT. Lion Mentari Airlines and its pilots employs standard clauses which fail to uphold the balance principle. There is an evident imbalance in the rights and obligations of the parties involved. Emphasizing the balance principle is crucial in standard contract agreements to address this disparity. The significance of this principle in work agreements extends to enhancing worker welfare, safeguarding against unjust practices, preventing illegal actions, strengthening industrial relations, and reducing workplace disputes. Overall, the study highlights the urgent need for equitable balance in work contracts to ensure fair and just treatment of all parties involved